2016
DOI: 10.1093/pasj/psw118
|View full text |Cite
|
Sign up to set email alerts
|

Projected axis ratios of galaxy clusters in the Horizon-AGN simulation: Impact of baryon physics and comparison with observations

Abstract: We characterize the non-sphericity of galaxy clusters by the projected axis ratio of spatial distribution of star, dark matter, and X-ray surface brightness (XSB). We select 40 simulated groups and clusters of galaxies with mass larger than 5 × 10 13 M ⊙ from the Horizon simulation that fully incorporates the relevant baryon physics, in particular, the AGN feedback. We find that the baryonic physics around the central region of galaxy clusters significantly affects the non-sphericity of dark matter distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 48 publications
8
34
1
Order By: Relevance
“…More recently, it was shown by Suto et al (2017) that baryonic physics operating in the cluster central region, such as cooling and feedback effects, can have a substantial impact on the non-sphericity of cluster halos up to half the virial radius, even though these baryonic effects have little impact on the spherically averaged DM density profile. They found that the DM distribution becomes more spherical, depending on the distance from the cluster center, when the effects of baryons are included.…”
Section: Comparison With λCdm Predictionsmentioning
confidence: 99%
“…More recently, it was shown by Suto et al (2017) that baryonic physics operating in the cluster central region, such as cooling and feedback effects, can have a substantial impact on the non-sphericity of cluster halos up to half the virial radius, even though these baryonic effects have little impact on the spherically averaged DM density profile. They found that the DM distribution becomes more spherical, depending on the distance from the cluster center, when the effects of baryons are included.…”
Section: Comparison With λCdm Predictionsmentioning
confidence: 99%
“…Cosmological effects related, for instance, to the growth rate and dark energy, may have an effect on the relative amplitude of moments. One could extend those measurements to cosmological hydrodynamical simulations in which baryonic physics, such as gas cooling and feedback from active galaxy nuclei, will substantially change the shape of the total mass distribution on small scales (Teyssier et al 2011;Suto et al 2017). These scales may be more efficiently probed by strong lensing observables (following, e.g.…”
Section: Redshift Mass Binmentioning
confidence: 99%
“…For example, the shape of dark matter distributions in galaxy clusters are affected by implemented baryon physics (e.g. Bett et al 2010;Schaller et al 2015;Bryan et al 2013;Suto et al 2017), which would be much rounder in all scales up to ∼ 1 Mpc without the feedback effect from the active galactic nucleus (AGN) (e.g. Suto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bett et al 2010;Schaller et al 2015;Bryan et al 2013;Suto et al 2017), which would be much rounder in all scales up to ∼ 1 Mpc without the feedback effect from the active galactic nucleus (AGN) (e.g. Suto et al 2017). Self interacting dark matter models predict more spherical distributions in the inner region of galaxy clusters than collisionless dark matter (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation